To solve the equation \( 4x^2 - 64 = 0 \) using the difference of squares pattern, we can first rewrite it in a form that highlights the difference of squares.
-
Start with the equation: \[ 4x^2 - 64 = 0 \]
-
Factor out the common term: \[ 4(x^2 - 16) = 0 \]
-
Now, we can use the difference of squares. Recall that \( a^2 - b^2 = (a - b)(a + b) \). Here, \( x^2 - 16 \) can be expressed as: \[ x^2 - 4^2 \]
-
Apply the difference of squares: \[ 4(x - 4)(x + 4) = 0 \]
-
Set each factor equal to zero: \[ x - 4 = 0 \quad \text{or} \quad x + 4 = 0 \]
-
Solve for \( x \): \[ x = 4 \quad \text{or} \quad x = -4 \]
Thus, the solutions to the equation \( 4x^2 - 64 = 0 \) are: \[ x = 4, \quad x = -4 \]
The responses matching this solution are:
- \( x = 4, ; x = -4 \)
- \( x \text{ equals } 4 ; \text{and} ; x \text{ equals } negative 4 \)
So the correct options would be: \( x = 4, ; x = -4 \)